2021
DOI: 10.1002/jev2.12080
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus membrane vesicles contain immunostimulatory DNA, RNA and peptidoglycan that activate innate immune receptors and induce autophagy

Abstract: Gram-positive bacteria ubiquitously produce membrane vesicles (MVs), and although they contribute to biological functions, our knowledge regarding their composition and immunogenicity remains limited. Here we examine the morphology, contents and immunostimulatory functions of MVs produced by three Staphylococcus aureus strains; a methicillin resistant clinical isolate, a methicillin sensitive clinical isolate and a laboratory-adapted strain. We observed differences in the number and morphology of MVs produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 91 publications
2
113
1
Order By: Relevance
“…NTA tends to measure biological EVs larger than that of TEM (Bachurski et al, 2019). The size of F. alocis EVs was similar to that of EVs derived from other Gram-positive bacteria (Bitto et al, 2021;Kim, Lee et al, 2020b). No colonies were observed after plating F. alocis EVs on Columbia agar (data not shown).…”
Section:  F Alocis Evs Induce Bone Loss In Vivomentioning
confidence: 83%
“…NTA tends to measure biological EVs larger than that of TEM (Bachurski et al, 2019). The size of F. alocis EVs was similar to that of EVs derived from other Gram-positive bacteria (Bitto et al, 2021;Kim, Lee et al, 2020b). No colonies were observed after plating F. alocis EVs on Columbia agar (data not shown).…”
Section:  F Alocis Evs Induce Bone Loss In Vivomentioning
confidence: 83%
“…BEVs (~20 nm to 400 nm) secreted by Gram-positive bacteria also contain sRNAs (<100 nt, with most in the range of 10 to 40 nt) [ 10 , 19 , 20 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Although recent studies have shown that sRNAs in BEVs affect host cell biology, to date no studies have identified specific sRNAs that mediate the host response to BEVs.…”
Section: Extracellular Vesicles Secreted By Bacteria Are Important Mediators Of Inter-kingdom Communication and Deliver Srna And Trna Framentioning
confidence: 99%
“…Staphylococcus aureus secretes sRNA and DNA in BEVs that have been implicated in inducing IFN-β mRNA by activation of Toll-like receptors in mouse macrophages [ 41 ]. S. aureus secrete BEVs that contain immunostimulatory DNA, RNA and peptidoglycan that activate innate immune receptors and induce autophagy in host A549 epithelial cells [ 40 ]. Although Mycobacterium tuberculosis (M.tb) is not considered a Gram-positive or Gram-negative bacterium, BEVs secreted by M.tb contain RNAs that promote IFN-b secretion upon entry into RAW 264.7 macrophages, which leads to M.tb clearance via activation of the macrophage RIG-I/MAVS signaling pathway [ 61 ].…”
Section: Extracellular Vesicles Secreted By Bacteria Are Important Mediators Of Inter-kingdom Communication and Deliver Srna And Trna Framentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanism behind the formation of MVs in Gram-positive bacteria is not fully understood, proteins involved in cell wall modification, like transpeptidases and autolysins are hypothesized to play an important role in the formation process, as these proteins have been detected in MVs released from Gram-positive bacteria [20][21][22] . Other contents of MVs include lipopolysaccharides 23 , peptidoglycan 24 , nucleic acids 24 , toxins 25 and proteins 26,27 . Some of the proteins identified in MVs were shown to be relatively enriched within the MVs when compared to their parent bacterium, suggesting a selective packing of proteins into the MVs 26,27 .…”
Section: Introductionmentioning
confidence: 99%